Track finding at Belle II - Bertacchi, Valerio; Bilka, Tadeas; Braun, Nils; Casarosa, Giulia; Corona, Luigi; Cunliffe, Sam; Dattola, Filippo; De Marino, Gaetano; De Nuccio, Michael; De Pietro, Giacomo; Van Dong, Thanh; Dujany, Giulio; et al. (Computer physics communications, 2021)
This paper describes the track-finding algorithm that is used for event reconstruction in the Belle II experiment operating at the SuperKEKB B-factory in Tsukuba, Japan. The algorithm is designed to balance the requirements of a high efficiency to find charged particles with a good track parameter resolution, a low rate of spurious tracks, and a reasonable demand on CPU resources. The software is implemented in a flexible, modular manner and employs a diverse selection of global and local track-finding algorithms to achieve an optimal performance.